2023
DOI: 10.1080/07853890.2023.2198775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of proton pump inhibitor use on clinical outcomes of patients with inflammatory bowel disease

Abstract: Objective Proton pump inhibitor (PPI) use has been associated with reduced diversity of the gut microbiome and may lead to worse clinical outcomes in inflammatory bowel disease (IBD). We aimed to evaluate whether PPI use affects clinical outcomes in a real-world setting. Design Healthcare claims data of adult IBD patients were obtained from the IBM MarketScan Database. Multivariable analysis and propensity score-matched analysis were performed to assess associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More prospective studies are needed to confirm these findings. A recent real-world study conducted in the US evaluated the influence of PPI use on the clinical outcomes of IBD patients[ 79 ]. This US study identified 46234 IBD patients, of whom 6488 used PPIs, while the remaining (39746 patients) did not use them.…”
Section: Clinical Epidemiology Of the Effects Of Ppis On Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…More prospective studies are needed to confirm these findings. A recent real-world study conducted in the US evaluated the influence of PPI use on the clinical outcomes of IBD patients[ 79 ]. This US study identified 46234 IBD patients, of whom 6488 used PPIs, while the remaining (39746 patients) did not use them.…”
Section: Clinical Epidemiology Of the Effects Of Ppis On Ibdmentioning
confidence: 99%
“…Compared to patients not on PPI therapy, those on concurrent PPI therapy were at a higher risk of developing undesirable clinical outcomes, such as new biologic initiation (OR = 1.11, 95%CI: 1.04-1.18), IBD-related admissions (OR = 1.95, 95%CI: 1.74-2.19), and surgeries (OR = 1.46, 95%CI: 1.26-1.71). Additionally, a dose-response relationship was noted between the number of PPI prescriptions and an increased risk of new biologic use and IBD-related admissions[ 79 ]. Hence, caution should be exercised when prescribing PPIs to IBD patients.…”
Section: Clinical Epidemiology Of the Effects Of Ppis On Ibdmentioning
confidence: 99%
“…In addition, a dose–response relationship indicated that high-dose PPI use was correlated with adverse outcomes. 53 …”
Section: Ast- Associated S Ide ...mentioning
confidence: 99%
“…The drug can reduce the secretion of gastric acid by gastric parietal cells by binding to H + -K + -ATPaseα. However, the combination of PPI and H + -K + -ATPase α is an irreversible process, so long-term use of the drug can cause a series of adverse reactions [31,32]. The application of cuttlebone in the treatment of CAG has the advantages of significant curative effect and small adverse reactions.…”
Section: Mechanism Of Cuttlebone In the Treatment Of Cagmentioning
confidence: 99%